Humanos, artisticamente humanos: as expressões da loucura como saber trágico de vidas excluídas pelos domínios da razão - Alves, Jadgleison Rocha (2020)
Among the possible reasons for the violations of rights linked to people in psychological distress, the political and normative construction within the International Law of Human Rights - reverberated in the concretization of Public Human Rights Policies - stands out among a reinforced scenario for a biopolitics inside out that aims to confine or exclude infectious germs from "social diseases" - including madness -, legitimizing a subhuman condition to depersonalized individuals in search of inhuman "social health". In this way, it brings at the top of the civilizing process the beacon of an immune logic, whose objective is to annihilate the “social disproportion” by affirming a single “hyper healthy” human face. It is within this political-normative-scientific territory that this dissertation has as main objective to present the discourses of madness from artistic expressions of interns at the Psychiatric Hospital Colônia Juliano Moreira in João Pessoa-PB as a critic and alternative to the exclusive domination of medical discourses -scientific. Specifically, the objectives of the study are: (1) to present and analyze the discourses of the artistic productions of individuals interned at the Psychiatric Hospital Colônia Juliano Moreira in João Pessoa-PB; (2) reflect on the historical-philosophical construction of a model of scientific domination of modern reason that annihilates tragic expressions; (3) criticize the biopolitical model exercised in modern times by the dynamics of the immune paradigm based on the experiences found with the inmates at Juliano Moreira; For this, the study presented a methodological option of qualitative aspect with analysis of moving images for the audiovisual and textual corpus, collected through the techniques of observation and documentary research. From the results obtained, it became possible to infer that the artistic expressions of men and women considered “crazy and crazy” who were hospitalized at the Psychiatric Hospital Colônia Juliano Moreira in João Pessoa-PB, reverberated a tragic knowledge whose power made it possible to present a way of escape that crosses the territorial confinement provided by biopower for a biopotent construction - inclusive and self-determined - in the formation of a culture of and for Human Rights outside the epistemological reduction of mental health.